Tourists' perception of capital cities : the case study of Zagreb, Croatia - Roberson, Donald N. (2008)
Summary: Tourism is an expanding industry throughout the world. Croatia has an extended history with tourism. Most tourists come to Croatia in order to visit the coastline with its many islands, blue sea, and ancient towns. The coastline of Croatia is a rare and beautiful destination. There are old towns, clear water, and a stunning contrast of sea and mountains. In addition, a multitude of islands, the native Mediterranean food, and clean sea help to sustain an attraction for travelers. Adding to this, the towns of Dubrovnik, Split, and Hvar are often in the headlines of popular tourist magazines. Yet, the often bypassed capital of Croatia, Zagreb, can be easily visited on the way to the coast. Therefore, it is important for the city of Zagreb to regularly gain information about tourists who visit Zagreb. Also, there is a need for the tourism industry of Croatia to include more than the Adriatic coast, especially the hinterlands as well as the capital city Zagreb. The purpose of this research is to understand English speaking tourist's specific recommendations for Zagreb, relying on qualitative research. Three researchers had 89 interviews with a total of 129 participants. This general qualitative research incorporated interviews as the main source of information. After analyzing the data, the findings indicate Zagreb as friendly, easy to get around, and as an old, quaint town with enjoyable activities. The main suggestion for the city of Zagreb was to find ways to improve the physical structure and provide more information for tourists
Bibliografija: 22 jed
Keywords: Turisti -- Hrvatska -- Stavovi; Turizam -- Zagreb